2005
DOI: 10.1029/2004jd005059
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐tropopause tracer transport in midlatitude convection

Abstract: [1] A three-dimensional cloud-resolving model is used to simulate the transport of lowertropospheric passive tracers into the lowermost stratosphere via midlatitude convection. In previous studies of troposphere-to-stratosphere convective transport the extent of irreversible transport is unclear because the tropopause location is difficult to determine in the highly perturbed environment directly above an active storm. To determine the irreversibility of cross-tropopause transport in this study, 10-hour simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 29 publications
(46 reference statements)
2
94
2
Order By: Relevance
“…Due to the fire emissions of sensible heat, latent heat in the form of water vapor, and aerosol particles that can act as cloud condensation nuclei (CCN), pyroCbs have unique dynamic and microphysical structures. It is well established that severe convection is an important mechanism for troposphere-to-stratosphere transport in the midlatitudes (Wang, 2003;Mullendore et al, 2005). Similarly, pyroCbs can reach to the upper troposphere and lower stratosphere (UT/LS) (Fromm and Servranckx, 2003;Fromm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fire emissions of sensible heat, latent heat in the form of water vapor, and aerosol particles that can act as cloud condensation nuclei (CCN), pyroCbs have unique dynamic and microphysical structures. It is well established that severe convection is an important mechanism for troposphere-to-stratosphere transport in the midlatitudes (Wang, 2003;Mullendore et al, 2005). Similarly, pyroCbs can reach to the upper troposphere and lower stratosphere (UT/LS) (Fromm and Servranckx, 2003;Fromm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Even though mid-latitude deep convection accounts for only a small fraction of the air masses in the lowermost extra-tropical stratosphere (Holton et al, 1995), this process is very important for the budgets of many trace species in the lower stratosphere, most notably water vapor as well as some short-lived species (Mullendore et al, 2005). This is due to the rapid and direct transport from the planetary boundary layer, where most tracers have their sources.…”
Section: Introductionmentioning
confidence: 99%
“…Lane et al (2003) and Lane and Sharman (2006) found that the breakdown of gravity waves generated by thunderstorms is an important source of turbulence above the cloud and at tropopause level. Mullendore et al (2005) assessed the vertical transport of idealized passive tracers by deep convection and found that, in addition to latent heating, mixing processes contribute significantly to potential temperature increases necessary for irreversible TST.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of ice and liquid hydrometeors are formed within the convective core, a significant amount of cloud mass is transported into the stratiform/anvil regime by upper level divergence and wind shear, where additional growth and particle collection may occur (Folkins, 2002;Mullendore, 2005). In addition, the actual contribution of the core to the total 25 cloud area compared to the stratiform/anvil regime is small, at ~1:7 (Liu and Fu, 2001) making consideration of dust effects on the stratiform regime important to the understanding of the large scale effects on the cloud fields reported in Min et al (2009) and Min and Li (2010).…”
Section: Psd Vertical Profile and Sedimentationmentioning
confidence: 99%